Expressão imuno-histoquímica das proteínas MMP-9, VEGF e FVW em lesões centrais e periféricas de células gigantes - Matos, Felipe Rodrigo de (2010)
Central giant cell lesion (CGCL) and peripheral giant cell lesion (PGCL) of the jaws have a distinct clinical behavior, although they share histopathologic features. It is still unclear whether these clinical differences are supported by a distinct pattern of immunoexpression of markers for multinucleated giant cells (GC) and mononuclear cells (MC). The purpose of this study was to compare the immunohistochemical expression of VEGF, MMP-9 in CG and MC and measure the vascularization by vWF to check whether there are differences in expression of these biomarkers between CGCL and PGCL. Paraffin wax blocks of 20 cases of LCCG and 20 LPCG were retrieved. MMP-9 immunoreactivity was greater in the CM of PGCL compared to VEGF (p<0.05). VEGF expression was greater in the CM of CGCL compared to PGCL (p<0.05) and it was greater in the overall expression of CGCL compared to PGCL (p<0.05). Vascularity was quantified by microvascular counting (MVC). MVC was greater in the PGCL compared CGCL (p<0.05). MMP-9 showed a greater tendency of expression in CGCL, though was not significant (p>0.05). We tested correlation between the proteins studied in each group and found a significant negative correlation between VEGF and vWF in CGCL (p<0.05). These results suggest that there are differences in the expression of VEGF in CM and overall expression between the lesions, although no statistically significant difference in the overall expression of the MMP-9. Then, there was a trend in increased expression of MMP-9 and VEGF in CGCL, possibly by the involvement of both proteins in osteoclastogenesis. Additionally, the results of this study indicate a higher degree of vascularization in PGCL compared to CGCL, fact that can be directly linked to the reactive nature of the PGCL, where the inflammatory process with its rich angiogenesis contributes significantly to these findings.